Biosynthesis of Zinc oxide nanoparticles from essential oil of Eucalyptus globulus with antimicrobial and anti-biofilm activities. (December 2020) - Obeizi, Zahra; Benbouzid, Houneida; Ouchenane, Sihem; Yılmaz, Deniz; Culha, Mustafa; Bououdina, Mohamed
Graphical abstract: Highlights: Biosynthesis of ZnO nanoparticles using Eucalyptus globulus essential oil. Characterizations of ZnO nanoparticles using XRD, DLS, FT-IR, SEM, EDX, TEM and UV-vis. Excellent antimicrobial and anti-biofilm activities. Mechanism for the formation of ZnO nanoparticles is proposed. Abstract: In this study, Eucalyptus globulus essential oil was used in green synthesis of Zinc oxide nanoparticles. After extraction of essential oil from leaves by hydrodistillation, it was mixed with Zinc acetate dihydrate to prepare ZnO nanoparticles. XRD, DLS, FTIR, SEM, TEM, EDX and UV-Vis were utilized to characterize the biosynthesized ZnO nanoparticles. X-ray diffraction analysis confirms the formation of single pure ZnO phase with an average crystallite size of 24 nm. SEM and TEM observations reveal irregular needle and spherical morphology with particle size at the nanoscale; meanwhile DLS analysis indicates a mean size around 40 nm. The antimicrobial activity was carried out by agar well diffusion method and by the determination of the minimum inhibitory concentration, whereas the anti-biofilm activity was investigated using 96-well microtiter plate method. The results indicate that ZnO NPs exhibit effective antimicrobial potential against all tested microorganisms with a maximum zone of inhibition of 19.35 ± 0.45 mm for K. pneumoniae at a concentration of 100 μg / ml. The significant percentage of biofilm inhibition was found 85% and 97% against S. aureus ATCC 25923 and P. aeruginosa ATCC 27853 biofilm, respectively. Possible mechanisms are proposed and discussed. This study demonstrates the importance of using essential oils for the easy and rapid green synthesis of ZnO nanoparticles with less use of toxic chemicals and exhibiting interesting biological activities with potential applications as efficient alternative to combat antibiotic resistance and eradicate bacterial biofilms from hospital environment.